2011
DOI: 10.1186/1471-2482-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Safety of liver resection and effect on quality of life in patients with benign hepatic disease: Single center experience

Abstract: BackgroundAlthough liver resection has long been established for selected patients with benign hepatic disease, the success of surgical treatment of these patients cannot be evaluated exclusively through postoperative morbidity and mortality. Therefore, the aim of the study was to prove the safety of liver resection in the treatment of benign liver tumors and to evaluate the effect of surgical treatment on the patients' qauality of life.MethodsA total of 146 patients who underwent liver resection because of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Of the 14 studies reviewed, three focused exclusively on patients with FNH . Nine further studies can be described as case series of hepatic resections performed for benign disease, including FNH . The remaining two studies reported on resections of both benign and malignant liver lesions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 14 studies reviewed, three focused exclusively on patients with FNH . Nine further studies can be described as case series of hepatic resections performed for benign disease, including FNH . The remaining two studies reported on resections of both benign and malignant liver lesions .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies included follow‐up data for 225 patients with benign disease including FNH . Five further studies, involving 143 patients, reported FNH‐specific morbidity and mortality statistics …”
Section: Resultsmentioning
confidence: 99%
“…This amount can be considered reasonable for an observational study, the more so as in recent literature regarding the subject, sample sizes comprising ranges of 40-179 patients have been used. 1,[21][22][23][26][27][28][29][30] In addition, bias was introduced as patients were not blinded or randomized to resection or not, since this obviously would not be a feasible study design. Resection might not always be possible, for example, for multiple or very large tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular adenomas most frequently occur in females at the age of years, and are associated with longstanding usage of oral contraceptives. [2][3][4][5] This is reflected in the annual incidence of [30][31][32][33][34][35][36][37][38][39][40] HCA per million in women with a history of oral contraceptive usage, versus 1 per million in women who never have used oral contraceptives. 5 Haemangiomas also occur most frequently in females, with a female/male ratio of 3:1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the retrospective design of the study and missing preoperative baseline QoL scores may have led to incorrect interpretation of the data. Until now, no prospective studies have addressed potential differences in long‐term QoL in patients who have undergone liver resection for benign compared with malignant diseases. The aim of this study was to investigate the effect of liver resection on QoL in patients undergoing surgery for benign or malignant tumours.…”
Section: Introductionmentioning
confidence: 99%